Methodological approaches applied to the collaborative development of a multiformat guide - Rodrigues dos Santos, Ana Rita; Romani, Elizabeth; Nunes Sobrinho, Francisco de Paula; Teixeira do Nascimento, Eriadne (InfoDesign, 2025)
The right to access information must be ensured in all contexts, particularly in educational institutions. This article outlines the methodological strategies for developing a multiformat guide for student support services at Federal University of Rio Grande do Norte (UFRN), emphasizing communication accessibility. Based on a Scoping Review and an inclusive design approach, the following research tools were used: two distinct focus groups and a co-creation tool. With the collaboration of a multidisciplinary team, the research identified significant barriers to information access, and its findings provided relevant data for developing guidelines that informed the guide’s creation.